Valuation impact of Sarbanes–Oxley: Evidence from disclosure and governance within the financial services industry - Akhigbe, Aigbe; Martin, Anna D. (Journal of Banking & Finance, 2006)
The Sarbanes–Oxley (Sarbox) legislation aimed to reduce the opacity of financial statements and improve the integrity of financial reporting by enhancing corporate disclosure and governance practices. We estimate the valuation effects of Sarbox for firms in the financial services industry and find that, except for securities firms, these firms significantly benefited from its adoption. As hypothesized, these positive effects may be attributed to expected improvement in the transparency of the relatively opaque financial services firms. We find that the cross-sectional variation in the valuation effects can be explained by disclosure and governance characteristics. Several of the significant factors are supportive of a compliance cost hypothesis. In particular, we find that the effects were less favorable for firms with less independent audit committees, without a financial expert on the audit committee, with less financial statement footnote disclosures, with less involved CEOs, and if they were smaller. In addition, reflecting the value of stronger governance, more favorable effects occurred for firms with a greater degree of independence of the board and the board committees, when there is greater motivation and ability of board members to monitor the firm, and with a greater degree of institutional ownership. Lastly, we find the wealth effects of firms viewed as non-compliant are significantly lower than firms viewed as compliant, and the variation across the group of non-compliant firms is explained by disclosure and governance measures.